The Level of Professional Development Among Faculty Members at Al-Balqa Applied University in Jordan - Al-Momani, Fakhri Falah Al-Ali; AL-Momani, Mohammad Omar (Journal of Posthumanism, 2025)
The objective of the study was to ascertain the extent of professional development among faculty members at Al-Balqa Applied University in Jordan, as perceived by the faculty members themselves, and to determine its correlation with the variables of gender and academic specialization of the faculty member. A descriptive approach was employed, and a questionnaire consisting of 16 items was utilized as the study tool. The questionnaire was administered to a study sample of 300 faculty members from Al-Balqa Applied University across its various faculties during the first semester of the academic year 2024/2025. The study's findings indicated that the faculty members' level of professional development was "medium," with an arithmetic mean of 3.13 and a standard deviation of 0.60. The study also found no statistically significant differences in the level of professional development attributable to the variables of gender (male, female) and academic specialization of the faculty member (humanities, science).